Im geschützten Raum: Musikförderung des Goethe-Instituts während der Militärdiktatur in Chile - Fugellie, Daniela (Die Musikforschung, 2021)
This article explores the musical events organized by the Goethe Institute during the Chilean dictatorship (1973–1990). An examination of the cultural and political discussions around these musical programmes demonstrates that the function of music as a tool for promoting democracy was understood in the context of the cultural activities of the Federal Republic of Germany in Chile. I explore the ways in which projects from the fields of jazz and contemporary music were understood as vehicles of democratic ideals, the consequences of the resulting musical transfers for the local musical life, as well as the shaping of a particular image of West Germany in Chile. (Vorlage)